Photosensitization of TiO2 Nanotube Arrays with Nanocrystalline Pbs - Lim, Ying-Chin; Munirah Hamdan, Nurul; Farah Atikah Harun, Nur; Ying Pei, Lim (International Journal of Engineering and Technology, 2019)
Narrow bandgap lead sulfide (PbS) nanoparticles, which may expand the light absorption range to visible region, have attracted tremendous interest serving as promising sensitizer in coupled semiconductor for photoelectrochemical cell. In this study, PbS were deposited onto titania nanotubes by successive ionic layer adsorption and reaction (SILAR) method. During the SILAR deposition, the growth of PbS onto titania nanotubes (PbS/TNT) had been tuned by tailoring the concentration of the precursor solution. The sample microstructure was characterized using Energy Dispersive X-Ray (EDX), Field Emission Scanning Electron Microscopy (FESEM) and X-Ray Diffraction (XRD). By varying the concentration of precursor solution, size and distribution of PbS nanoparticles could be tuned. Upon growth of PbS onto TNT, all samples showed enhanced photocurrent response ascribed to the changes in microstructure and optical properties of the synthesized samples. At 100 mM solution concentration dipped for 5 SILAR cycles, the sample demonstrated the highest peak photocurrent density of 890 mA/cm2 and a corresponding photoconversion efficiency of 0.55% compared to the as-prepared TNT (36 mA/cm2). The PbS/TNT composite could be considered as an excellent photoelectrode material applied in the solar conversion devices due to its high visible light harvesting capability.